A war like no other : - Bush, Richard C. (John Wiley & Sons, 2007)
In dense, academic prose, Brookings Institution scholars O'Hanlon and Bush argue that a war with China is neither as implausible as it might appear nor as inevitable as history would suggest. The likely cause for military intervention, they propose, would come not from China's rise as a regional and global power, nor from the growing threat it poses to the U.S.'s economic strength, nor from its curtailment of human rights-all of which could be addressed diplomatically-but rather the political situation of Taiwan, the semi-autonomous island 100 miles from the mainland, whose independence could upset delicate U.S-China relations. The authors present a number of possible conflict scenarios and discuss the sorts of legislative and diplomatic action that could get the U.S. into them, but wisely avoid bombast by noting regularly that war with China remains unlikely. The only passages of general interest here are those on Taiwanese history; the legislative and diplomatic prescriptions that constitute the majority of the book, while comprehensive and reasonable, will fail to excite even interested lay readers. Professors and lawmakers would do well to read this volume, if only for the reminder that, in this time of seemingly insuperable international dilemma, some problems can still be solved with a bit of level-headed diplomatic maneuvering.